Safe laparoscopic cholecystectomy technique and timing for acute cholecystitis: a study in India - Uchintala, Venkata Sai Sreenivas; Srinivasan, Uma Sankar; Syed, Tajuddin; Prabhu, Eswar Gollahalli; Selvam, Shaktivel (International Surgery Journal, 2023)
Background: Acute cholecystitis patients undergo laparoscopic cholecystectomy (LC) within 72 hours or 6 weeks to 12 weeks after onset is widely considered the optimal timings for LC. However, there has been no clear consensus about it. We aimed to determine safe technique of LC for acute cholecystitis within 72 hours or any time of presentation with no delay in surgery. Methods: Medical records of 100 patients who underwent standard LC were reviewed retrospectively. Patients were divided into group 1, patients undergoing LC within 72 hours of onset; group 2, between 4 days to 14 days; group3, between 3 weeks to 6 weeks; group 4, more than 6 weeks. Results: No significant differences existed between groups in conversion rate to open surgery, operation time, blood loss, or postoperative morbidity, and hospital stay. However, total hospital stays in groups 1 and 2 was significantly shorter than that in groups 3 and 4 (p<0.01). In addition, the total hospital stay in group 3 was also significantly shorter than that in group 4 (p<0.01). Conclusions: Best timing of LC for acute cholecystitis may be within 72 hours, and there is no need to delay LC in patients presenting after 72 hours and with safe technique of dissecting at infundibulum retrieval of stones and cystic duct stump closure with catgut loop there is no significant difference observed retrospectively.